Fiber optics communications (Prentice Hall, 1992)
Explaining the basic concepts of communicating using optical fibre transmission lines, this book covers system design, operating principles, characteristics and application of the components that comprise fibre-optic systems. Relevant topics from communications theory, electronics and optics are developed as needed. This third edition includes new topics including optical solutions, fibre and semiconductor optical amplifiers, optical isolators, improved laser diodes, new tranmission standards, wavelength-dependent couplers and advances in optical integrated circuits for fibre networks. The book should be of use to those on courses in fibre optics in departments of electrical engineering or electronic technology.